Does reduced MHC diversity decrease viability of vertebrate populations? - Radwan, Jacek (Biol Conserv, 2010)
Loss of genetic variation may render populations more vulnerable to pathogens due to inbreeding depression and depletion of variation in genes responsible for immunity against parasites. Here we review the evidence for the significance of variation in genes of the Major Histocompatibility Complex (MHC) for conservation efforts. MHC molecules present pathogen-derived antigens to the effector cells of the immune system and thus trigger the adaptive immune response. Some MHC genes are the most variable functional genes in the vertebrate genome. Their variation is clearly of adaptive significance and there is considerable evidence that its maintenance is mainly due to balancing selection imposed by pathogens. However, while the evidence for selection shaping MHC variation on the historical timescale is compelling, a correlation between levels of MHC variation and variation at neutral loci is often observed, indicating that on a shorter timescale drift also substantially affects MHC, leading to depletion of MHC diversity. The evidence that the loss of MHC variation negatively affects population survival is so far equivocal and difficult to separate from effects of general inbreeding. Some species with depleted MHC variation seem to be particularly susceptible to infection, but other species thrive and expand following severe bottlenecks that have drastically limited their MHC variation. However, while the latter demonstrate that MHC variation is not always critical for population survival, these species may in fact represent rare examples of survival despite of the loss of MHC variation. There is clearly a compelling need for data that would disclose the possible consequences of MHC diversity for population viability. In particular, we need more data on the impact of MHC allelic richness on the abundance of parasites or prevalence of disease in populations, while controlling for the role of general inbreeding. Before such evidence accumulates, captive breeding programs and other conservation measures aimed at inbreeding avoidance should be favoured over those protecting only MHC variation, especially since inbreeding avoidance programs would usually conserve both types of genetic diversity simultaneously.